(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents the results of the analysis of psychological and pedagogical literature on the problem of forming the readiness of future specialists in the field of “Physical Culture and Sports” in higher education institutions for professional activity, reveals the basic concepts of readiness considered by modern psychological and pedagogical science, groups the professional skills of future specialists in the field of “Physical Culture and Sports” (gnostic - the ability to analyze literary sources and scientific concepts; to research the object, process and result of one’s work; to analyze social situations and their impact on personal development; to study individual characteristics of different age groups of people, motives of their behavior; this is knowledge and awareness that help a person to effectively develop their physical qualities, apply training methods and lead a healthy lifestyle; Design skills - the ability to formulate a goal and a system of tasks for the optimal performance of professional activities, to predict a program of individual development, to model the content, forms and methods of activity and possible situations, models of human behavior; the ability to plan, develop and organize physical education and recreation activities taking into account individual capabilities, goals and modern training methods. Design skills allow you to effectively build the educational and training process, improve sports achievements and promote a healthy lifestyle; constructive - the ability to implement certain tasks, choose productive forms, methods and techniques in working with different groups and categories of people; to determine the goal and plan ways to improve professional activity; the ability to create, modify and adapt physical education and sports activities in accordance with specific conditions, goals and capabilities of participants; communication - the ability to build optimal relationships, show tolerance, kindness, emotional stability and optimism in any conditions; the ability to effectively interact with participants in the sports process, motivate them, transfer knowledge and adjust their activities to achieve better results; organizational - the ability to create conditions for achieving the goal and fulfilling tasks; to teach ways to navigate in various stressful situations and solve problems; to make optimal independent decisions; the ability to effectively plan, coordinate and manage physical education and sports activities, ensuring its quality and achievement of goals; evaluative - the ability to determine the effectiveness of one’s own activities, control one’s own actions, psychological state, behavior and professional relationships, the ability to analyze, control and correct the level of physical fitness, technical skills and general condition of athletes or participants in physical education classes. The essence and specificity of the readiness of future specialists for professional activity are revealed, the structure of readiness for professional activity is defined, two main approaches to defining the content of the concept of “readiness for activity” are distinguished - functional and personal.